Work Climate in Early Care and Education and Teachers' Stress: Indirect Associations through Emotion Regulation - Jeon, Lieny; Ardeleanu, Katherine (Early education and development, 2020)
Teaching is a highly stressful profession due to many stressors that teachers experience. To understand how early childhood teachers internally handle work climate-related stressors, we examined associations between teacher-perceived work climate, teachers' use of emotion regulation strategies, and the degree of stress that teachers experience. Using a sample of 1,129 preschool-aged classroom teachers across the United States, we found that teacher-perceived work climate variables (i.e., work situations, support from families, children's challenging behaviors) were all directly associated with teachers' stress. Second, when teachers reported better work climate and support from families, they used a higher degree of reappraisal emotion regulation strategies. In addition, when teachers had more children with challenging behaviors, they utilized more suppression emotion regulation strategies. In turn, teachers' emotion regulation strategies were significantly associated with their stress. Practice or Policy: Our study suggests that reappraisal emotion regulation strategies have benefits for dealing with environmental stressors and are related to decreased stress. The study has policy and practice implications for ensuring adequate access to mental health resources for teachers in order to manage emotional stress. In addition, a positive work climate for teachers can be fostered. Such interventions could result in improved teacher well-being and performance.